If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + 2u = 56 Solving 16 + 2u = 56 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 2u = 56 + -16 Combine like terms: 16 + -16 = 0 0 + 2u = 56 + -16 2u = 56 + -16 Combine like terms: 56 + -16 = 40 2u = 40 Divide each side by '2'. u = 20 Simplifying u = 20
| 0.4x+0.96=2.96 | | X^2=7/4 | | -17/5= | | 13f+8=19f-17f-3 | | 120-40/7-5=x | | 3b+4=b+19 | | 4e-8=19 | | 4x-9=3(x+5) | | 4a=8-5a | | 7-16m=-20m-17 | | 0.9-0.45= | | 5=17-4n | | 4y+3=6y+8 | | 83-v=274 | | 8.2x-57.4=-24.6 | | 10v+5v=25 | | 15n-25n+8n=18 | | 4g-13=3 | | 3(4z+9)=20-7z | | 24-c=2(3) | | 8y-5y=-27 | | -12n-12=-11n | | (-4v+3)(8v+6)=0 | | 9400=10 | | 9y-4y-14=48.80 | | 8.2x-53.4=-24.6 | | (t)=4t+3t^3+2t-7 | | -28-3n=8+6n | | X/5=33 | | 4v-13=59 | | 7b+8=4b-10 | | 4x+24=17 |